PENGARUH MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING (SFAE) BERBANTUAN MEDIA POP-UP BOOK TERHADAP PEMAHAMAN KONSEP IPAS SD NEGERI 76 PALEMBANG - Aprilia Agusti, Leni; Yulaini, Erma; Riyanti, Henni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Student Facilitator and Explaining (SFAE) learning model assisted by Pop-Up Book media on the understanding of the concept of science at SD Negeri 76 Palembang. The research method used is a quantitative experiment of the Quasi Experimental Design type with a Nonequivalent Control Group Design research design. The population in this study were all 51 students of grade IV of SD Negeri 76 Palembang. The research sample consisted of 25 students of grade IV A as the experimental class and 26 students of grade IV B as the control class, with the sampling technique using saturated sampling technique. Data collection techniques used were tests, questionnaires and documentation. The average posttest in the experimental class was 82.4 (high) greater than the control class 73.2 (moderate). The results of the questionnaire of 84.35% were included in the positive category. The data analysis technique used was the Independent Sample T-test. From the results of the hypothesis test with the help of the SPSS 26 program, the calculated t value was 2.799 > t table 2.009 with a sig value (2-tailed) of 0.007 (<0.05). This shows that Ho is rejected and Ha is accepted, so it can be concluded that there is an influence of the Student Facilitator and Explaining (SFAE) learning model assisted by Pop-Up Book media on the understanding of the concept of science at SD Negeri 76 Palembang.